Associations of high-sensitivity C-reactive protein with neuropsychological outcomes and cerebral white matter hyperintensities in older adults at risk of dementia - Rachael Yu; Shawn D. Kong; Catriona Ireland; Genevieve Z. Steiner-Lim; Kimberley Bassett; Hannes Almgren; Dongang Wang; Chenyu Wang; Johannes C. Michaelian; Sharon L. Naismith (Brain, Behavior, & Immunity - Health)
Inflammation is becoming increasingly recognised as a core feature of dementia with evidence indicating that its role may vary and adapt across different stages of the neurodegenerative process. This study aimed to investigate whether the associations of high-sensitivity C-reactive protein (hs-CRP) with neuropsychological performance (verbal memory, executive function, processing speed) and cerebral white matter hyperintensities (WMHs) differed between older adults with subjective cognitive decline (SCD; n = 179) and mild cognitive impairment (MCI; n = 286). Fasting serum hs-CRP concentrations were grouped into low (<1.0 mg/L), moderate (1.0–3.0 mg/L), and high (>3.0–10.0 mg/L). Structural MRI scans were used to estimate WMH lesion volumes in the whole brain, as well as periventricular, deep white matter, and frontal regions. After adjusting for relevant demographic and clinical factors, multiple regression analyses revealed that in participants with SCD, high hs-CRP concentrations were significantly associated with poorer executive function (β[95% CI] = −.20[−.65, −.04], p = .025) and processing speed (β[95% CI] = −.19[−.53, .00], p = .048). Exploratory analyses suggested that this effect may be specific to APOE-ε4 non-carriers only. There were no significant associations between hs-CRP and neuropsychological outcomes in those with MCI. Hs-CRP was not associated with WMH volumes. Our findings suggest that hs-CRP may be involved in early disruptions to cerebral frontal-subcortical pathways, particularly in APOE-ε4 non-carriers, though this association may be independent of white matter lesions. In the earliest stages of cognitive decline where subjective complaints are paramount, addressing inflammation may offer potential benefits for supporting cognitive health.